Multiple natural hazards at volcanic islands: a review for the Ischia volcano (Italy) - Selva, J.; Acocella, V.; Bisson, M.; Caliro, S.; Costa, A.; Della Seta, M.; De Martino, P.; de Vita, S.; Federico, C.; Giordano, G.; Martino, S.; Cardaci, C. (Journal of applied volcanology, 2019)
Volcanic islands pose several major types of natural hazards, often interconnected and concentrated in relatively small areas. The quantification of these hazards must be framed from a multi-hazard perspective whilst building on existing single-hazard analyses. Ischia is a densely inhabited volcanic island with a long eruptive history lasting more than 150 ka (last in 1302 AD) characterized by the significant asymmetric resurgence of a caldera block. Here, we review the state-of-art of the natural hazards of Ischia, aiming at building a solid base for future holistic multi-hazard quantifications. We frame our analysis in three steps: i) review of geological, historical and current activity; ii) review of available hazard models and analyses; iii) development of an interpretative framework for the interdependent hazards. The results highlight that volcanic activity has been quite intense and many volcano-related hazardous phenomena have affected the island including in very recent times, both for eruptive (phreatic or magmatic eruptions) and non-eruptive (earthquakes, landslides, and tsunamis) phenomena. The effects of some of them (e.g. tsunamis, tephra) are also relevant beyond the island territory. Quantitative hazard assessments are almost absent and should be developed in the future considering the evident interconnections between hazards. To this end, we propose a conceptual interpretative multi-hazard framework that highlights the fundamental role played by the resurgent block in controlling and connecting the different hazards, in terms of both spatial distribution of the sources and temporal clustering.